NILAI LAMBU MBOIDE DALAM BLUE ECONOMY PENGELOLAHAN EKOWISATA HIU PAUS DI DESA BOTUBARANI, GORONTALO - M, Fitri Nurhayati; Amaliah, Tri Handayani; Mahdalena (Sebi : Studi Ekonomi dan Bisnis Islam, 2025)
Whale shark ecotourism in Botubarani Village, Bone Bolango Regency, is one of the rapidly developing marine tourism destinations and contributes significantly to the welfare of coastal communities. However, tourism development that focuses on increasing visitor numbers has the potential to create ecological pressure on the sustainability of whale sharks (Rhincodon typus), thereby necessitating tourism governance oriented toward sustainability. This study aims to analyze the role of the cultural value of Lambu Mboide in strengthening blue economy principles in the management of whale shark ecotourism in Botubarani. The research employs a descriptive qualitative approach using a literature study method, through the review of academic journals, scientific reports, and supporting documents related to Botubarani, the blue economy, and Gorontalo local wisdom. The findings indicate that blue economy principles have been reflected in ecotourism management through the limitation of tourist–whale shark interactions, the empowerment of local communities, and a conservation-oriented approach as the foundation of the coastal economy. The value of Lambu Mboide, which encompasses the spirit of collectivity, mutual cooperation, and harmony between humans and nature, has proven to function as social capital that strengthens community-based tourism governance. This local wisdom encourages communities to safeguard the sustainability of whale shark habitats and to distribute economic benefits equitably. Thus, the integration of cultural values and blue economy principles constitutes a model of ecotourism management that not only maintains ecological balance but also strengthens the economic self-reliance of local communities. This study implies that conservation approaches grounded in local cultural values can serve as an effective strategy for the sustainable management of marine tourism destinations